Longitudinal sleep problem trajectories are associated with multiple impairments in child well‐being. (26th July 2020) - Williamson, Ariel A.; Mindell, Jodi A.; Hiscock, Harriet; Quach, Jon
Abstract : Background: This study examined whether distinct sleep problem trajectories from infancy through middle childhood were associated with multiple aspects of child well‐being at ages 10–11 years. Methods: Data were from the first six waves of the Longitudinal Study of Australian Children – Birth Cohort (5, 107 children recruited at birth). Caregivers reported on child sleep problems at each time point. A combination of caregiver‐reported, teacher‐reported and child‐completed tasks were used to index child well‐being outcomes at ages 10–11 years including emotional/behavioural functioning (internalizing and externalizing symptoms; self‐control), health‐related quality of life, cognitive skills and academic achievement. Results: Latent class analysis identified five distinct sleep problem trajectories over time: persistent sleep problems through middle childhood (7.7% of the sample), limited infant/preschool sleep problems (9.0%), increased middle childhood sleep problems (17.0%), mild sleep problems over time (14.4%) and no sleep problems (51.9%). Compared to those with no sleep problems, children with persistent sleep problems had the greatest impairments across all outcomes except cognitive skills (perceptual reasoning), with moderate to large effect sizes. Children with increased middle childhood sleep problems similarly experienced greater internalizing and externalizing symptoms and worse quality of life, but few academic impairments. Both the limited infant/preschool sleep problems and mild increases over time trajectories also showed internalizing concerns and worse caregiver‐reported quality of life, although effects were smaller than the other sleep trajectories. Conclusions: The linkages between sleep problems and negative child outcomes across domains underscore the importance of early identification and targeted intervention to address sleep problems and promote child well‐being.